Isolation and characterisation of 2-Tert-butyl-8-hydroxyquinoline as a crystalline solid and its blue fluorescent Li complex - Kathirgamanathan, Poopathy; Surendrakumar, Sivagnanasundram; Ravichandran, Seenivasagam; Blake, Alexander J. (Hindawi Publishing Corporation, 2014)
2-Tert-butyl-8-hydroxyquinoline (2-TB-8-hq) has been isolated as a crystalline solid and its X-ray structure elucidated, resolving three decades of controversy, since it was previously wrongly reported as yellow oil by some other workers. An improved synthetic method has been developed which increases the yield from 20% to 60%. The lithium complex of 2-TB-8-hq is blue emitting and the HOMO and LUMO levels are lowered by 0.86 eV and 0.74 eV, respectively, compared with the parent lithium 8-hydroxyquinolinolate (Li 8-hq).